2016
DOI: 10.1016/j.jacc.2016.07.766
|View full text |Cite
|
Sign up to set email alerts
|

PITX2 Modulates Atrial Membrane Potential and the Antiarrhythmic Effects of Sodium-Channel Blockers

Abstract: BackgroundAntiarrhythmic drugs are widely used to treat patients with atrial fibrillation (AF), but the mechanisms conveying their variable effectiveness are not known. Recent data suggested that paired like homeodomain-2 transcription factor (PITX2) might play an important role in regulating gene expression and electrical function of the adult left atrium (LA).ObjectivesAfter determining LA PITX2 expression in AF patients requiring rhythm control therapy, the authors assessed the effects of Pitx2c on LA elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
124
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(144 citation statements)
references
References 47 publications
(73 reference statements)
15
124
0
4
Order By: Relevance
“…This locus is near the paired‐like homeodomain transcription factors ( PITX2 ) gene, which is critical for left‐right asymmetry of the pulmonary vein (PV) . Recent studies have shown that changes in PITX2c RNA levels can lead to a change in atrial membrane potential . Anatomically, the PV are an important source of triggers for the initiation of AF and a main target of catheter‐based treatment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This locus is near the paired‐like homeodomain transcription factors ( PITX2 ) gene, which is critical for left‐right asymmetry of the pulmonary vein (PV) . Recent studies have shown that changes in PITX2c RNA levels can lead to a change in atrial membrane potential . Anatomically, the PV are an important source of triggers for the initiation of AF and a main target of catheter‐based treatment .…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies have shown that changes in PITX2c RNA levels can lead to a change in atrial membrane potential. 3,4 Anatomically, the PV are an important source of triggers for the initiation of AF and a main target of catheter-based treatment. 5 However, there are no data regarding 4q25 variants and how they impact left atrial substrate.…”
mentioning
confidence: 99%
“…Further, reduced function of the transcription factor encoded by PITX2 has been associated with AF, shortening of the left atrial action potential, and with modulation of sodium channel blocker therapy in the adult left atrium. 2224 A transcriptional co-regulatory network governed by transcription factors encoded by TBX5 and PITX2 has been shown to be critical for atrial development. 25 …”
mentioning
confidence: 99%
“…These noncoding Jiake He et al, Variants on chromosome 4q25 are associated with increased risk of AF after catheter ablation variants existed in close proximity (~150 kb) to the cis-regulatory region of paired-like homeodomain transcription factor 2 (PITX2), and modulated PITX2 activity through transcription level as postulated [25,26]. PITX2 efficiently regulated atrial resting membrane potential and involved in the formation, differentiation and proliferation of pulmonary myocardium [27,28]. Three isoforms of PITX2 (PITX2a, PITX2b, and PITX2c) have been identified, among which PITX2c was the only isoform expressed in the left atrium [29].…”
Section: Discussionmentioning
confidence: 99%